Chaperone suppression of alpha-synuclein toxicity in a Drosophila model for Parkinson's disease. - Auluck, P.K.; Chan, H.Y.; Trojanowski, J.Q.; Lee, V.M.Y.; Bonini, N.M. (Science, 2002)
Parkinson's disease is a movement disorder characterized by degeneration of dopaminergic neurons in the substantia nigra pars compacta. Dopaminergic neuronal loss also occurs in Drosophila melanogaster upon directed expression of alpha-synuclein, a protein implicated in the pathogenesis of Parkinson's disease and a major component of proteinaceous Lewy bodies. We report that directed expression of the molecular chaperone Hsp70 prevented dopaminergic neuronal loss associated with alpha-synuclein in Drosophila and that interference with endogenous chaperone activity accelerated alpha-synuclein toxicity. Furthermore, Lewy bodies in human postmortem tissue immunostained for molecular chaperones, also suggesting that chaperones may play a role in Parkinson's disease progression.